How Tourism Can (and Does) Benefit the Poor and the Environment - A Case Study from Panama - Klytchnikova, Irina I.; Dorosh, Paul A. (World Bank, Washington, DC, 2012)
Tourism is one of Latin America's fastest growing industries, outranking remittances and even drugs in many countries as a source of foreign exchange. But the impact of tourism on the poor and on the environment remains under debate. Certainly many suspect that tourism does more harm than good, damaging the environment and leaving the poor worse off while shipping profits overseas. But few have actually analyzed the impact of tourism on the economy of a developing country. In this En Breve, Irina Klytchnikova and Paul Dorosh describe a study on the economic costs and benefits of tourism which they carried out as part of a country environmental assessment in Panama. As a country marked by a 'dual economy', Panama shares with other Latin American countries a fast growing, modern urban sector side by side with impoverished rural and peri-urban populations. Tourism has been growing in Panama and contributes somewhere between 6 and 9 percent of gross domestic product (GDP). More importantly, Klytchnikova and Dorosh found that as a sector, tourism has large multiplier effects on the Panamanian economy and has the potential for significant benefits to the poor and to the environment. But tourism's poverty benefits are neither automatic nor ubiquitous. They depend on where and how supply chains are structured and on the way tourists spend their money. This 'En Breve' presents the results of an assessment of the tourism sector based on a top-down model. The results bode well for tourism in Panama, and could be a model for analysis in other Latin America and the Caribbean (LAC) countries.